Study of catalyst layers for carbon nanotubes growth - Chandrasekaran Amuthavijayan (2008)
Carbon nanotubes (CNTs) have attracted much attention due to their exceptional electrical, optical, mechanical properties and attractive potential application. A series of carbon nanotube (CNT) arrays are synthesized by acetylene dissociation over two different catalyst seed layer are also deposited by two different methods (RF sputtering method and FCVA method). By varying the process parameters the physical characteristics of the carbon nanotubes, which are diameter, density, and length can be varied. Some of the process parameters are substrate temperature, growth time and the hydrocarbon concentration. Besides the process parameters, the catalyst also plays an important role in growth of carbon nanotube. Catalyst layer controls the physical properties of CNT such as diameter, density and length.